“To assess the level of anxiety, depression and coping strategy in diabetic mellitus patients.’’ - Potdar, Nutan J.; Patil, Sangita Sidojirao; Pawar, Shivaji; Choudhari, Samir K.; Bhosale, Tejas; Pawar, Ajit Anandrao (International Journal of Psychosocial Rehabilitation, 2020)
As the general population individuals with diabetes are nearly double as probably to suffer from anxiety and depression. 6 but this is not recognized early so not treated early.1 Therefore, there is a necessity to assess the level of anxiety, depression and coping strategy in diabetic mellitus patients.Study assessed the level of anxiety, depression and coping strategy in diabetic mellitus patients.A descriptive survey approach and non-experimental research design was adopted in this study. A survey of 50 patients, selected from hospitals in western Maharashtra by purposive sampling. After obtaining permission from the setting, the patients’ willingness was considered to participate in the study and informed consent was obtained. After collecting the demographic data, Structured questionnaire to assess the Anxiety, Back’s depression scale to assess depression and Brief COPE scale to assess coping strategies was used. According to Anxiety scale 90% diabetic mellitus patients were having mild anxiety, 94% diabetic mellitus patients were having severe depression. 90 % of diabetic mellitus patients were using coping strategy. Patients of diabetic mellitus experiences severe anxiety and depression, nurse should focus on the patient care to attained the optimal quality of life.